Peran Pergadaian terhadap Kesejahteraan Masyarakat (Study pada Pegadaian Syariah Kusumanegara) - Fais, Rusdyansah Noersan (Universitas Pendidikan Ganesha, 2025)
The purpose of this study is to determine the procedures for the implementation of Sharia Pawn (Gadai Syariah) at the Syariah Pawnshop Office of Kusumanegara, and to find out how effective the Sharia Pawnshop is in improving the welfare of the Yogyakarta community. The method used is qualitative research. The data used consists of primary and secondary data. Primary data were obtained through direct observation, direct interviews in the field, and activities related to the research problem. Secondary data were obtained from the Syariah Pawnshop Office of Kusumanegara and other sources. The data analysis used, because this research is qualitative in nature, is inductive analysis—an analysis approach that starts from specific phenomena or events and then draws general conclusions. The results of the study show that the practice of Sharia Pawn at the Kusumanegara Syariah Pawnshop is in accordance with the principles of Sharia pawning as stipulated in the Qur’an and Hadith, namely the absence of interest (riba) practices. The impact of the Sharia Pawnshop practice on the economic life of the Yogyakarta community can be categorized into two: positive and negative impacts. The positive impact is for people who pawn their goods as marhun (collateral) at the Kusumanegara Syariah Pawnshop with the aim of obtaining business capital, especially for lower-middle-income communities. The negative impact is for people who pawn their goods as marhun solely for the purpose of fulfilling temporary consumption needs.